Light‐induced regulation of ligand‐gated channel activity - Bregestovski, Piotr (Br J Pharmacol, 2017)
The control of ligand‐gated receptors with light using photochromic compounds has evolved from the first handcrafted examples to accurate, engineered receptors, whose development is supported by rational design, high‐resolution protein structures, comparative pharmacology and molecular biology manipulations. Photoswitchable regulators have been designed and characterized for a large number of ligand‐gated receptors in the mammalian nervous system, including nicotinic acetylcholine, glutamate and GABA receptors. They provide a well‐equipped toolbox to investigate synaptic and neuronal circuits in all‐optical experiments. This focused review discusses the design and properties of these photoswitches, their applications and shortcomings and future perspectives in the field. LINKED ARTICLES: This article is part of a themed section on Nicotinic Acetylcholine Receptors. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.11/issuetoc